The bonnie baby: Experimentally manipulated temperament affects perceived cuteness and motivation to view infant faces - Parsons, C; Young, K; Bhandari, R; van Ijzendoorn, M; Bakermans-Kranenburg, M; Stein, A; Kringelbach, M (2014)
Attractive individuals are perceived as having various positive personality qualities. Positive personality qualities can in turn increase perceived attractiveness. However, the developmental origins of the link between attractiveness and personality are not understood. This is important because infant attractiveness ('cuteness') elicits caregiving from adults, and infant personality ('temperament') shapes caregiving behaviour. While research suggests that adults have more positive attitudes towards cuter infants, it is not known whether positive infant temperament can increase the perception of infant cuteness. We investigated the impact of experimentally established infant temperament on adults' perception of cuteness and desire to view individual faces. Ataseline, adults rated the cuteness of, and keypressed to view, images of unfamiliar infants with neutral facial expressions. Training required adults to learn about an infant's 'temperament', through repeated pairing of the neutral infant face with positive or negative facial expressions and vocalizations. Adults then re-rated the original neutral infant faces. Post-training, there were significant changes from baseline: infants who were mostly happy were perceived as cuter and adults expended greater effort to view them. Infants who were mostly sad were not perceived as cuter and adults expended less effort to view them. Our results suggest that temperament has clear consequences for how adults perceive 'bonnie' babies. Perception of infant cuteness is not based on physical facial features alone, and is modifiable through experience. © 2013 John Wiley and Sons Ltd.